Indian food and welfare schemes: Scope for digitization towards cash transfers - Shweta Saini; Sameedh Sharma; Ashok Gulati; Siraj Hussain; Joachim von Braun (Indian Council for Research on International Economic Relations (ICRIER), 2017)
The paper presents a case for a phased rolling out of direct benefits transfer (DBT) for Food in India. By studying all states and Union Territories on three broad parameters: demographics, performance of the existing Public Distribution System (PDS), and current state of banking infrastructure, the paper evaluates their "readiness" for shifting away from the existing physical grain distribution system under PDS to the ICT based DBT where a food subsidy amount (in lieu of PDS grain entitlement) is directly transferred into the Aadhaar-linked bank account of identified beneficiaries. The analysis reveals that all 36 states can implement DBT-food in the next five years i.e. by the year 2022 and this should happen in four phases. The states that are urban, have sufficient open market grain availability, are financially inclusive, and have lesser percentage of poor and malnourished may make the shift almost immediately. For rest, an interim phase of a reformed and IT based PDS system with identity verification of beneficiaries is built-in. In order to make the transition to DBT feasible and successful, the paper recommends improvements and investments by states/UTs into ensuring adequate food grains in the open markets, inclusive banking infrastructure and diverse payment channels, sufficiency of the food subsidy amount and display of leadership and political will to reform the PDS through DBT. This paper argues that DBT has a potential to make way for a system of social security or universal basic income, where every citizen receives income support - the size of which can be adjusted based on his/her needs and vulnerability.
Keywords: Q18; Q01; I38; E64; D61; H53; 330; National Food Security Act (NFSA); FCI; Cash Transfers; CCTs; Financial Inclusion; direct benefit transfer (DBT); Public Distribution System (PDS); Indian agriculture; Aadhaar; JAM; Grain Leakages